PENGARUH SELF CONTROL, DISIPLIN BELAJAR, DAN DOOMSCROLLING TERHADAP PROKRASTINASI AKADEMIK MAHASISWA: SEBUAH LITERATURE REVIEW - Manek, Alfridus; Butar-Butar, Agustina (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Academic procrastination is one of the most common problems among university students and may negatively affect academic achievement, time management, and study completion. The rapid development of digital technology has introduced new factors that are believed to influence academic procrastination behavior, one of which is doomscrolling. This study aims to examine the relationship between self-control, learning discipline, and doomscrolling on students’ academic procrastination through a literature review approach. The articles analyzed were obtained from various scientific sources, including Google Scholar, Garuda, and relevant national and international journals. The findings indicate that self-control and learning discipline have a negative relationship with academic procrastination. Students who possess strong self-control and good learning discipline tend to manage their time effectively, complete academic tasks on schedule, and reduce procrastination behavior. In contrast, doomscrolling shows a positive relationship with academic procrastination. Excessive social media use and overconsumption of digital information can cause students to lose focus, decrease productivity, and increase their tendency to delay academic tasks. The findings suggest that academic procrastination is influenced by a combination of internal and external factors. Therefore, strengthening self-control and learning discipline should be accompanied by the ability to manage digital media use wisely in order to reduce academic procrastination among university students.